Obesity in Indonesian and Taiwanese Adolescents Related to Self Perception, Diet, Exercise, and Body Image - Fauzi, Lukman; Handayani, Oktia Woro Kasmini; Susilo, Mursid Tri; Kurnia, Arif Rahmat; Rahayu, Sri Ratna; Irawan, Fajar Awang; Jing-Horng Lu, Frank; Lin, Cenyi; Lai, Mei Fen; Chiao Yu, Ya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Obesity prevalence in Asia was raising. Self-perception became an increasingly determinant predictor of a healthier lifestyle. The purpose of this study was to investigate the relationship between self-perception and actual BMI among Indonesian and Taiwanese teenagers. This research was cross sectional and using participatory sampling of 415 participants from 6 high schools in Indonesia, and 717 participants from 7 high schools in Taiwan. The data was taken by enumerator using the Obesity Impact on the Quality of Life Perception Questionnaire (ObI-Q) and the Projective Test. Self-perception was statistically associated with actual BMI which state that obesity might be treated by hospital, clinics, or specialist (p0.001). Self-perception was also related to degenerative disease (p = 0.003) and social life (p = 0.04). Self-perception about sports stated that obese people could be as good as normal people (p=0.11). Most teenagers had the correct perception regarding ideal body image (p=0.04). The multivariable analysis showed that teenagers who did not have self-perception of desire to lose weight were 6.37 times more likely to have overweight than teenagers who had self-perception of desire to lose weight. Self-perception of desire to lose weight was a variable with major contribution to actual BMI among teenagers.